Partners in Play: Examining Parent-Teacher Collaboration on Preschoolers’ Cognitive Growth - Nofianti, Rita; Waeno, Mahamadaree; Rita Nofianti (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga, Yogyakarta, 2025)
This study investigates how deliberate, play-centred collaboration between parents and preschool teachers influences children’s cognitive development, addressing a research gap on coordinated home–school play strategies in Indonesian early childhood settings. Using a mixed-methods quasi-experimental design, 92 preschoolers (M = 5.1 years), 8 classroom teachers, and 92 parents from 4 urban preschools participated in an 8-week Partners in Play intervention. Parent–teacher dyads co-planned weekly play modules aligned with Vygotskian guided-play principles. Children’s working memory, verbal reasoning, and cognitive flexibility were assessed using adapted WPPSI-IV subtests before and after the intervention. At the same time, observational rubrics and parent play logs triangulated quantitative gains with qualitative insights. ANCOVA was used to test mean-score differences, and thematic coding in NVivo 14 examined communication patterns. Children in the intervention group outperformed controls in working memory (η² = 0.18) and cognitive flexibility (η² = 0.12). At the same time, gains in verbal reasoning approached significance (p = .07). Qualitative findings identified three reinforcing mechanisms: a shared play language that scaffolded metacognition; consistent cognitive challenges across home and school contexts; and reciprocal feedback loops that enabled weekly refinement of play activities. Reported barriers included limited parental time and teachers’ initial uncertainty in co-designing home-based activities. Although the modest sample size and urban focus limit generalisability, the findings offer an evidence-based, low-cost implementation model for early childhood programmes through brief co-planning workshops, a shared play glossary, and simple progress-sharing tools. This study contributes to broader debates on home–school partnership and play-based learning in early childhood education by providing experimental evidence that structured parent–teacher collaboration functions as an active cognitive scaffold within guided play, and is relevant beyond Indonesia because similar challenges of fragmented learning environments and uneven family engagement are evident across diverse ECE contexts.